Applying a Nonspin-Flip Reaction Scheme to Explain for the Doublet Sulfide Oxides SMO2 Observed for the Reactions of SO2 with V(4F), Nb(6D), and Ta(4F). (1st April 2018) - Velásquez, Carlos; Torres, Ana E.; Seminario, Jorge M.; Colmenares, Fernando
Abstract : Energy profiles linking the reactants M + SO2 (M = V( 4 F), Nb( 6 D; 4 F), and Ta( 4 F)) with the products observed for these reactions under matrix-isolation conditions, mainly the oxide complex OV(η2 -SO) and the sulfide oxides SVO2, SNbO2, and STaO2, have been obtained from DFT and CASSCF-MRMP2 calculations. For each of these interactions, the radical fragments MO + SO can be reached from the lowest-lying quadruplet electronic states of the reactants. As the quadruplet and doublet radical asymptotes that vary only in the spin of the unpaired parallel electrons of the nonmetallic fragment are degenerated, a second reaction leading to the rebounding of the radical fragments can take place through both multiplicity channels. Reaction along the doublet pathway leads in each case to the most stable structure for the oxide SMO2 . For the vanadium interaction, recombination of the radical species through the quadruplet channel explains for the oxide product OV(η2 -SO).